Distressed yet bonded: A longitudinal investigation of the COVID-19 pandemic’s silver lining effects on life satisfaction. - Guan, Yanjun; Jiang, Da; Wu, Chaorong; Deng, Hong; Su, Shangyao; Buchtel, Emma E.; Chen, Sylvia Xiaohua (American Psychologist, 2025)
It is a common understanding that the 2019 coronavirus pandemic (COVID-19) significantly harmed mental health. However, findings on changes in overall life satisfaction have been mixed and inconclusive. To address this puzzling phenomenon, we draw upon the domain specific perspective of well-being and research on catastrophe compassion and propose that the pandemic can have opposing effects on mental health and communal satisfaction, which then differently relate to people’s overall life satisfaction. Longitudinal analyses of the Household, Income and Labour Dynamics (HILDA) Survey of Australia (N = 12,093) showed that while there was a greater decrease in mental health in the first COVID-19 pandemic year (2019-2020) than in previous years (2017-2019), an increase in communal satisfaction also occurred, demonstrating a potential silver lining effect of the pandemic on people’s satisfaction with family, community and neighborhood. Moreover, consistent with socioemotional selectivity theory, changes in mental health, communal satisfaction and life satisfaction were related to age such that older adults generally reported less harmful and more beneficial psychological changes. We further found that age was associated with stronger associations of mental health and communal satisfaction with life satisfaction during the pandemic year. Overall, our findings speak to the importance of communal life in life satisfaction during the pandemic and age-related differences in the process, shedding light on the need to devise customized support to address inequalities in pandemic effects on public well-being.
Keywords: General Psychology; General Medicine